Hacia una didáctica del sentido. Didácticas emergentes de las prácticas pedagógicas de filosofía en tres escuelas católicas (2017)
Given the lack of clarity exerted by philosophy as scholar learning, this investigation look for identify the underlying pedagogical practices in philosophy, in order to analize the didactic problems of teaching philosophy or teaching philosophizing. The qualitative aproach of the investigative exercise, has made possible an approach to three catholic schools contexts, and to the comprehension of students and teachers that share a philosophical academical space. The epistemological and hermeneutical perspective, conciliates the distant relationships among protagonists that are at the philosophical classroom, in order to propose a didactic of sense, where the significance of philosophy, meet whith the signifiers, in other words with the philosophers students, to built a full of sense knowledge. This text shows the first category of investigations developement , which names philosophy's didact.